NILAI PATRIOTIK DALAM AJARAN BUSHIDO DI JEPANG - Sri Sudarsih (Diponegoro University, 2018)
Bushido as a moral teaching contains the principles of virtue to form the soul of a knight. A typical Japanese knight is a Samurai. The moral teaching is inherited verbally from generation to generation until now. Japanese people practice these teachings seriously into everyday life. They live every principle with full sincerity, honesty, and wholeheartedly to form a patriotic soul. The principles of teaching are formulated in writing into seven principles that are inseparable from one another. Because every principle underlies and animates other principles. A Samurai cannot abandon one principle of teaching because if he abandons one principle the quality of a samurai will disappear so that he does not have a patriotic soul. Therefore, Bushido is able to form a patriot who is always superior.